P005: Pre-hospital dexamethasone administration in children with croup: the Edmonton experience. (2nd June 2016) - Ali, S.; Moodley, A.; Bhattacharjee, A.; Lobay, K.; Chang, E.; Kabaroff, A.; Allain, D.
Abstract : Introduction: Croup is one of the most common childhood respiratory illnesses, affecting more than 80, 000 Canadian children per year. Early dexamethasone administration in croup can reduce admission rates and length of stay (LOS), as well as return visits to the emergency department (ED). Pre-hospital emergency medical services (EMS) teams in Edmonton administer dexamethasone to children with croup. The objectives of this study were to (a) assess the clinical impact of pre-hospital administration of dexamethasone to children with croup and (b) compare clinical outcomes of these patients to those who did not receive their first dose of dexamethasone via the EMS providers.Methods: This study was a retrospective medical record review that included children between 6 months and 6 years of age who were brought via EMS to the Stollery Children's Hospital ED with a final diagnosis of croup, between January 1st 2010 and December 31 st 2012. Data were collected regarding pre-hospital presentation and management, ED presentation and management, ED LOS and final disposition, and patient demographics.Results: 188 patients were enrolled, 35.1% (66/188) of whom received a pre-hospital diagnosis of croup. The mean age of the participants was 32.96 months (SD±17.18). Overall, 10.6% patients (20/188) were given dexamethasone in the pre-hospital setting, while 30.3% patients (57/188) were given nebulized epinephrine by EMS. Out of the 66 patients with a pre-hospital diagnosis of croup, 10.6% (n=7) were given dexamethasone by EMS. In the ED, dexamethasone was administered to 88.3% of patients (166/188) while 56/188 participants (29.8%) received nebulized epinephrine. There was no statistically significant difference in ED LOS stay between those who received pre-hospital dexamethasone (2.6 hours, SD±1.6, n=18) and those who did not (3.3 hours, SD±2.7, n=159). The number of in-hospital epinephrine doses per patient was influenced by the administration of pre-hospital dexamethasone (p=0.010).Conclusion: Pre-hospital administration of dexamethasone likely influences the severity and short-term persistence of croup symptoms, as evidenced by less epinephrine use in the ED. Contrary to current EMS guidelines, very few patients with a pre-hospital diagnosis of croup received dexamethasone by EMS personnel. This likely represents a missed opportunity to decrease the severity of the patients' disease.